2013
DOI: 10.1088/2040-8978/15/12/125402
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of exit pupil function: improvement on the OTF of full parallax holographic stereograms

Abstract: The wavefront reconstructed errors of full parallax holographic stereograms are analysed. The optical transfer function (OTF) is simulated to investigate frequency response and imaging quality of holographic stereogram systems. The behaviour of the OTF with respect to slit size and spatial frequency in different aberrations is described and used to optimize the exit pupil function. The shaped window function (Gaussian and Blackman) is proposed to be used as the exit pupil function of holographic systems, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…In our previous study, the wavefront reconstructed errors in the holographic stereogram were expressed as defocusing aberrations, and the frequency responses of the full-parallax holographic stereogram were studied when the Rectangle, the shaped Gaussian, and the shaped Blackman window functions were used as the exit pupil functions, respectively. The design criterion of the exit pupil function was then discussed [72]. Moreover, exit modeling and OTF analysis of the EPSIM-based holographic stereogram were carried out [38].…”
Section: Frequency Response Analysis Of the Holographic Stereogrammentioning
confidence: 99%
“…In our previous study, the wavefront reconstructed errors in the holographic stereogram were expressed as defocusing aberrations, and the frequency responses of the full-parallax holographic stereogram were studied when the Rectangle, the shaped Gaussian, and the shaped Blackman window functions were used as the exit pupil functions, respectively. The design criterion of the exit pupil function was then discussed [72]. Moreover, exit modeling and OTF analysis of the EPSIM-based holographic stereogram were carried out [38].…”
Section: Frequency Response Analysis Of the Holographic Stereogrammentioning
confidence: 99%
“…作者简介: 蒋晓瑜(1967-) 系统。Takaki 等 [6] 提出了一种通过物体多个角度的视差图像而直接生成全息体视图的方法。2013 年, Hong 等 [7] 开发了一种类似于 "点" 打印的全息体视图的打印系统, 并采用全息单元交叠的方法提高再现视差图像的 成像质量。在国内, 北京理工大学王涌天教授课题组、 刘娟教授课题组在全息显示的采样、 编码、 调制以及波 前像差的优化方法等方面取得了一系列的进展 [8][9][10][11] 。北京邮电大学桑新柱等 [12][13] 研究了利用全息功能屏实现 具有平滑运动视差的全息体视系统。清华大学 Zhang 等 [14][15] 研究组结合光学点源追迹与全息体视方法, 实现 了可正确表达会聚、 遮挡效果的全视差全息体视图。随着全息体视图系统的不断发展, 尤其是在全息体视图 打印过程中, 通过改进三维物体视差图像的拍摄方法 [3] , 优化出瞳函数 [16] 、 利用全息单元交叠法 [7] , 像素抽取法 和视角切片法 [17] 对视差图像进行预处理 [18] 、 改进全息体视图构建方法等, 不断地减小视差图像的失真率, 提高 全息体视图的分辨率和成像质量。全视差全息体视图的本质是由体视图平面产生一系列的波前片段来无限 逼近真实物体的波前, 所以在全息体视图成像时重建的波前并不是物体的真实深度, 因而存在波前误差, 这种 波前误差表现为离焦像差, 所以全息体视图成像系统的出瞳形状、 大小尺寸影响着成像质量, 而它又决定于全 息体视图打印平台中孔径光阑的大小和形状。本文构建了一种基于全息单元的全视差全息体视图成像系统 模型, 对该成像系统模型的边端性质及光学传递函数 [19][20] 进行了相关分析; 并以矩形函数为该成像系统的光瞳…”
Section: 引 言unclassified
“…[13] This function could be determined by the shape, size, and transmittance of the hogel, and optimizing the amplitude and phase filters can improve the optical resolution. In 2013, Jiang et al [14] investigated the influence of different shaped windows on the optical transfer function (OTF) of holographic stereogram systems. Their analysis showed that the shaped exit pupil function, with optimized hogel size, can effectively improve the imaging quality of full-parallax holographic stereogram systems.…”
Section: Introductionmentioning
confidence: 99%